Using Wordwall Application to Improve Vocabulary Mastery at MTs DDI Cambalagi (Maros) - Fathurrahmi, Nur; Muliati, A.; Asriati, Asriati (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study aimed to determine whether using the Wordwall application improves students' vocabulary mastery. This research used a quantitative method with a pre-experimental design and a one-group pretest-posttest design. The population of this research was made up of students from class VIII MTs DDI Cambalagi, totalling five classes. The sample in this research was a class VIII D consisting of 28 students. The sample in this research was selected by cluster random sampling. The research instrument used was a vocabulary test of 35 questions. A vocabulary test was conducted before treatment (pretest) and after treatment (posttest), and the Wordwall application was used as a learning medium for three meetings. The results of the data analysis demonstrated that the mean score of the students’ pretest was 39.07, while the mean score of the students’ posttest improved to 77.46. Furthermore, the analysis paired sample t-test results demonstrated a statistically significant improvement, with the result of the sig. (2-tailed) value is .000 < 0.05. Based on the data analysis, the results found that the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. This indicates that using the Wordwall application is effective and can be a viable option for improving students’ vocabulary mastery. Consequently, the Wordwall application can be integrated as an engaging and interactive learning tool to improve students’ vocabulary mastery at MTs DDI Cambalagi (Maros).